The Introduction of the Euro and its Effects on Investment Decisions - Rainer Haselmann; Herwartz Helmut (Kiel University, Department of Economics, 2005)
In this paper we examine changes on investment decisions induced by the introduction of the Euro. There are two potential sources of portfolio reallocation. First, the introduction of the Euro diminished exchange rate risks within the EMU region, which relieved European investors from currency risk associated with intra-EMU investments. Second, monetary policy has been bundled within one single institution, which increased the correlation of different national stock and bond market returns. We test for structural breaks in the portfolio holdings of German investors and estimate a market model in the latter in order to account for the two described effects. We observe a significant decrease in national and an significant increase in intra-EMU as well as US investments. Therefore, the establishment of the EMU led to a decrease of investment home bias.
Keywords: G15; F36; F33; F21; 330; investment home bias; realized volatility; Euro introduction; Portfolio-Investition; Anlageverhalten; Euro; Währungsumstellung; Portfolio-Management; Internationaler Finanzmarkt; Schätzung; Deutschland; EU-Staaten; home bias